MELATIH KECERDASAN KINESTETIK MELALUI PERMAINAN KREATIF TANGKAP BOLA UNTUK ANAK USIA DINI - Iriani, Ani; Westhisi, Sharina Munggaraning (IKIP Siliwangi, 2021)
The background in this study is about kinesthetic intelligence in early childhood, where kinesthetic intelligence is still low, due to the lack of strength of children in coordinating hand and foot movements. Kinesthetic intelligence is very influential in stimulating children's physical growth and development. Children who master kinesthetic movement intelligence tend to have good body coordination. Therefore, a fun learning process is needed that can improve kinesthetic intelligence, one of which is through creative catch ball games. The purpose of this research is to determine children's activities in improving kinesthetic intelligence through creative game catching ball at the Taan Bani Umar institution. The research method used is descriptive qualitative research with 15 students from TAAM Bani Umar as the subject. Data collection techniques are taken through observation, interviews and documentation. The instrument used is in the form of an observation checklist sheet that contains indicators that can be used to regulate the concept of children's kinetic intelligence. While the data analysis consists of data reduction, data presentation, tringulation. Based on the results of the research, the planning was carried out by the teacher by preparing the curriculum, carried out with full sincerity and was able to mimic the motion of throwing and catching the ball, and the result of the development of the indicator was that the child was able to control himself in throwing and catching the ball on the spot or beside the body.Latarbelakangpada penelitian ini tentang kecerdasankinestetik pada anak usia din, dimana kecerdasan kinestetik ini masih rendah, karena kurangnya kekuatan anak dalam mengkoordinasikan gerakan tangan dan kaki. Kecerdasan kinestetik sangat berpengaruh untuk merangsang pertambahan dan perkembangan fisik anak. Anak yang menguasai kecerdasan gerak kinestetik cenderung koordinasi tubuhnya baik Oleh sebab itu diperlukan suatu pembelajaran menyenangkan yang dapat meningkatkan kecerdasan kinestetik, salah satunya melalui permainan kreatif tangkap bola. Tujuan dilakukannya penelitian ini yaitu untuk mengetahui aktivitas anak dalam meningkatkan kecerdasan kinestetik melalui permainan kreatif tangkap bola di lembaga Taan Bani Umar . Metode penelitian yang digunakan adalah deskritif kualitatif dengan subjek penelitian 15 peserta didikdari TAAM Bani Umar. Teknik pengumpulan data yang diambil melalui observasi, wawancara dan dokumentasi. Instrumen yang digunakan berupa lembar ceklis observasi yang berisi indikator-indikator yang dapat digunakan untuk mengatur konsep pada kecerdasan kinenstetik anak. Sedangkan analisis datanya terdiri dari reduksi data, penyajian data, tringulasi. Berdasarkan hasil penelitian, perencanaan dilaksanakan guru dengan menyiapkan kurikulum, dilaksanakan dengan penuh kesungguhan dan dapat menirukan gerakan melempar dan menangkap bola, dan hasil perkembangan indikatornya adalah anak mampu mengontrol diri dalam melempar dan menangkap bola ditempat maupun disamping badan.